Experimental study of inclusion expediency of the white willow extractin the hydrogel of anti-arthrosis action - D. V. Kompantsev (Бюллетень сибирской медицины)
The analysis of acute toxicity and anti-inflammation activity of the willow extract is performed expediency of its inclusion in the preparations with anti-arthrosis activity. The dose dependent study of anti-inflammatory activity of willow extract was carried out of the model of acute inflammatory swelling which was provoked by introduction of 0.1 ml of 10% kaolin in the hind leg of the rat. Comparative anti-inflammatory activity of glucosamine sulphate and hydrogel in experimental osteoarthrosis was studied by modeling of inflammation. Most marked anti-inflammatory activity was shown to have the willow extract in the doses of 100 and 200 mg/kg. Inclusion of the willow extract in granules increased anti-proliferative activity of glucosamine in experimental osteoarthrosis. Combined use of the willow extract with glucosamine more effective than monotherapy by glucosamine, influenced suppressively on proliferative stage of inflammation in experimental osteoarthosis.